OUTSOURCING UNITED NATIONS PEACEKEEPING ROLES AND SUPPORT FUNCTIONS - Charles, K A; Cloete, C E (The South African Journal of Industrial Engineering, 2009)
The paper examines the use of private security organisations in a peacekeeping role as a cost-effective and efficient alternative to United Nations (UN) peacekeepers, and develops an outsourcing scorecard for the UN. Forty national and international organisations were surveyed through questionnaires, a review of relevant